Social classes, ideology, and national issue in the debate between the FAR and the PRT-ERP (Tempo e Argumento, 2016)
The purpose of this paper is addressing the main argumentative cores in the debate between the Fuerzas Armadas Revolucionarias (FAR) and the Partido Revolucionario de los Trabajadores-Ejército Revolucionario del Pueblo (PRT-ERP), two armed organizations in the 1970s. The discussion took place between April and November 1971 and its trigger was a report on the FAR published by the serial Cristianismo y Revolución. This document was followed by “Responde el ERP,” a brief replica prepared by political prisoners, and then the response by the FAR with its “Aportes al proceso de confrontación de posiciones y polémica pública que abordamos con el ERP.” In this paper, we address in detail the role assigned in the debate to social classes, to deepen its relation with other topics, such as the national issue and ideology. We are interested in studying the meaning of these categories from the viewpoint of historical players, to track which ideological and discursive constellation they are in.